An autopsy case of vagus nerve stimulation following acupuncture. Issue 2 (March 2015) - Watanabe, Mayumi; Unuma, Kana; Fujii, Yusuke; Noritake, Kanako; Uemura, Koichi
Highlights A male in his late forties died right after acupuncture treatment. We found severe haemorrhaging around the right vagus nerve in his neck. We discuss the relationship between vagus nerve stimulation and the cause of death. We review a few fatal acupuncture cases. This is the first report of a death due to vagus nerve stimulation after acupuncture.